Gagasan Amandemen Ulang Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Harry Setya Nugraha (Universitas Islam Indonesia, 2018)
AbstractIdeally, the constitution of a state must conform to the values of constitutionalism. However, the Indonesian constitution (1945 Constitution of the Republic of Indonesia) is currently inconsistent with the values of constitutionalism. This can be seen from the bias of presidentialism and the vagueness of the legislative chamber system applied in Indonesia as to whether it relies on a three-chamber or two-chamber parliamentary system. This article examined the ideal design of presidential government and parliamentary systems in Indonesia. Using the juridical-normative research method, this study recommended five ideas that should be employed as the materials for changes in the 1945 Constitution of the Republic of Indonesia to actualize a more authentic presidential system. Additionally, in an effort to reinforce the two-chamber parliamentary system in Indonesia, the first step taken should be to shift the People’s Consultative Assembly (MPR) paradigm from previously being known as an institution with its exclusive membership to being acknowledged as a joint meeting forum between the House of Representatives (DPR) and Regional Representative Council (DPD). Furthermore, to achieve an ideal two-chamber parliamentary system, DPR and DPD must be positioned in the same level in terms of their functions and authorities.Keywords: The Fifth Amendment to the 1945 Constitution of the Republic of Indonesia; presidential; two-chamber parliament AbstrakDalam tatanan ideal, konstitusi suatu negara haruslah sejalan dengan nilai-nilai konstitusionalisme. Namun realitanya saat ini, konstitusi negara Indonesia (UUD NRI 1945) masih belum sejalan dengan nilai-nilai konstitusionalisme itu sendiri. Hal ini dapat dilihat dari biasnya bangunan presidensialisme di Indonesia serta tidak jelasnya sistem kamar parlemen yang diterapkan di Indonesia, apakah berkayuh pada sistem parlemen tiga kamar ataukah pada sistem parlemen dua kamar. Artikel ini mengkaji bagaimana desain ideal sistem pemerintahan presidensil dan kamar parlemen di Indonesia. Dengan metode penelitian yuridis-normatif, penelitian ini menyimpulkan bahwa, terdapat 5 gagasan yang perlu menjadi materi perubahan dalam UUD NRI 1945 dalam rangka mewujudkan sistem presidensil yang lebih murni. Selain itu, dalam upaya mempertegas parlemen dua kamar di Indonesia, langkah pertama yang harus dilakukan adalah merubah paradigma MPR yang semula dianggap sebagai sebuah lembaga yang memiliki keanggotaan tersendiri, menjadi MPR yang merupakan forum sidang gabungan antara DPR dan DPD. Selanjutnya, agar sistem parlemen dua kamar yang digagas menjadi lebih ideal, DPR dan DPD haruslah diposisikan dalam strata yang sama dalam hal fungsi dan kewenangannya.Kata-kata Kunci: Perubahan kelima UUD NRI 1945; presidensil; parlemen dua kamar